Bilinear elastoplastic constitutive model with polyvinyl alcohol content for strain-hardening cementitious composite. (10th June 2019) - Zhang, Chuanchuan; Yang, Xinhua
Highlights: A bilinear elastoplastic constitutive model with the PVA content is proposed for SHCC. Higher fiber volume fraction has a better modification on performance of SHCC pipe. Conventional steel reinforcement can be replaced with the PVA fiber (>1.25%). Abstract: Strain-hardening cementitious composite (SHCC) exhibits good tensile hardening performance and polyvinyl alcohol (PVA) content has a significant effect on its tensile properties. A bilinear elastoplastic constitutive model with the PVA content is proposed for SHCC and validated by comparison with the experimental data available in the open literature. In order to quantitatively evaluate the PVA content effect, the deformation responses of SHCC pipes with various volume fractions of PVA fiber not larger than 2.00% to the three-edge-bearing load were numerically simulated. It is found that both the ultimate load and the maximum plastic energy of SHCC pipe can be remarkably enhanced by adding PVA fibers. Moreover, compared to the fiber content less than 1%, they are improved more obviously when the fiber content is greater than 1%. Accordingly, higher fiber volume fraction has a better modification effect on the structural performance of SHCC pipe. In addition, the conventional steel reinforcement can be replaced with the PVA fiber reinforcement when the volume fraction of PVA fibers is greater than 1.25%.